Behaviour of Stock Return Autocorrelation in the GCC Stock Markets - Chowdhury, H.; Rahman, A.; Sadique, Shibley (Sage Publications, 2014)
There is overwhelming evidence of the presence of autocorrelation in stock returns in many previous studies. Since stock return correlation is related to predictability of stock prices, it is important to know the extent of autocorrelation and its underlying causes. This article investigates the autocorrelation structure of seven Gulf Cooperation Council (GCC) stock markets. All the markets except for Dubai and Kuwait show significant first-order autocorrelation of returns. Bahrain, Oman and Qatar exhibit strong positive whereas Abu Dhabi exhibits negative autocorrelation of returns. In general, return autocorrelation conditional on a negative return day is higher than that conditional on a positive return day. Autocorrelation between weekdays is usually larger than that between the first and last trading day of the week. Use of dynamic volatility models gives evidence that for almost all the markets negative feedback traders are the dominant players to contribute to the autocorrelation of returns. Thus, traders are very keen to realize their profits too often, resulting in significantly positive return autocorrelation.